2021
DOI: 10.1186/s13567-021-00949-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of increasing challenge with Eimeria maxima on the growth performance and gene expression of biomarkers associated with intestinal integrity and nutrient transporters

Abstract: This study was conducted to investigate the impacts of graded severity of Eimeria maxima infection on the growth performance and intestine health of broiler chickens. Four different levels of E. maxima-challenged treatments were used, including a non-challenged control group, a low challenge (12 500 oocysts), a medium challenge (25 000 oocysts), and a high challenge dose (50 000 oocysts). There were eight replicate cages per treatment, with 12 birds in each cage, and chickens in the challenged groups orally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 50 publications
10
45
0
Order By: Relevance
“…GLUT2, located at the basolateral side, takes over the sugar absorption transport once inside the cell and mediates the passive transport of glucose, fructose, and galactose out of enterocytes into the bloodstream [ 38 , 39 ]. Others have similarly observed the downregulation of intestinal GLUT2, GLUT5, and SGLT1 in Eimeria - and Campylobacter jejuni -challenged birds [ 7 , 22 , 37 , 40 ]. In the current study, amino acid transporters CAT2 and y+LAT1 were also downregulated in Eimeria -challenged groups regardless of the dietary fiber and protein levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…GLUT2, located at the basolateral side, takes over the sugar absorption transport once inside the cell and mediates the passive transport of glucose, fructose, and galactose out of enterocytes into the bloodstream [ 38 , 39 ]. Others have similarly observed the downregulation of intestinal GLUT2, GLUT5, and SGLT1 in Eimeria - and Campylobacter jejuni -challenged birds [ 7 , 22 , 37 , 40 ]. In the current study, amino acid transporters CAT2 and y+LAT1 were also downregulated in Eimeria -challenged groups regardless of the dietary fiber and protein levels.…”
Section: Discussionmentioning
confidence: 96%
“…The objective of the two experiments reported herein was to investigate the potential and mechanisms of exogenous enzymes action on mitigating the negative effects of Eimeria challenge on growth performance, gene expression of tight junctions and nutrient transporters, and cecal fermentation pattern. Eimeria -induced reduction in broiler growth performance is positively correlated with infective dose [ 21 , 22 ]. Bodyweight gain of birds at 1 to 6 DPI (day 14 to day 20) can be linearly reduced from 27% to 49% when challenged by increasing oocysts doses of mixed Eimeria spp.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 ] and Teng et al . [ 36 ]. Furthermore, SGLT1 inactivation and GLUT2 downregulation were also observed in the enterocytes of rats exposed to different physical stressors [ 37 , 38 ], and in the jejunum of broiler chicken exposed to HS [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, while differences were observed in gastrointestinal permeability, it was only less than two-fold difference. Our previous study [ 37 ] reported that more than 200 folds differences of gastrointestinal permeability were observed due to E. maxima infection. Hence, reduced VFA production in the ceca due to E. tenella infection caused energy deficiency in the body, which resulted in compensated gut health in broiler chickens.…”
Section: Discussionmentioning
confidence: 99%